2011
DOI: 10.1007/s00216-011-5099-8
|View full text |Cite
|
Sign up to set email alerts
|

Drug detection in breath: effects of pulmonary blood flow and cardiac output on propofol exhalation

Abstract: Breath analysis could offer a non-invasive means of intravenous drug monitoring if robust correlations between drug concentrations in breath and blood can be established. In this study, propofol blood and breath concentrations were determined in an animal model under varying physiological conditions. Propofol concentrations in breath were determined by means of two independently calibrated analytical methods: continuous, real-time proton transfer reaction mass spectrometry (PTR-MS) and discontinuous solid-phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 27 publications
1
49
0
Order By: Relevance
“…Kamysek et al investigated the influence of changes in cardiac output on expiratory propofol concentrations in seven pigs [5]. Using on-line PTR-MS and discontinuous solid-phase micro-extraction coupled with gas chromatography mass spectrometry they found that a decrease in cardiac output during continuous propofol infusion did not deteriorate the relationship between propofol breath and blood concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kamysek et al investigated the influence of changes in cardiac output on expiratory propofol concentrations in seven pigs [5]. Using on-line PTR-MS and discontinuous solid-phase micro-extraction coupled with gas chromatography mass spectrometry they found that a decrease in cardiac output during continuous propofol infusion did not deteriorate the relationship between propofol breath and blood concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is currently no method of doing so. In contrast, propofol concentration in exhaled breath can be detected and measured during anesthesia by various techniques [1][2][3][4][5][6][7][8]. These techniques range from discontinuous techniques like thermal desorption gas chromatography-mass spectrometry (analytical time hours to days) [2,9] to fast discontinuous methods like solid-phase microextraction coupled with gas chromatography mass spectrometry or ion mobility spectrometry coupled to a multicapillary column for pre-separation (analytical time within minutes) [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such improvements in sampling, analysis and statistical validation have led to the indication that concentration changes are more important than unique breath biomarkers111213. At present, online monitoring of instant physiological changes in exhaled VOC profiles is possible with the required analytical sensitivity or resolution, which also enables clinicians to relate different biochemical and metabolic processes to exhaled VOCs2891415161718.…”
mentioning
confidence: 99%
“…There are few reports on specific compounds and the analysis of volatile organic compounds during the whole composting process (Li and Huang, 2006;Nasini et al, 2016;Shen et al, 2012;Tiquia and Tam, 1998). HS-SPME-GC-MS has strong analytical capabilities for volatile organic substances and has qualitative and quantitative analysis applications in medical (Gentili et al, 2004;Kamysek et al, 2011), environmental (Higashikawa et al, 2013;Kotowska et al, 2012;Menendez et al, 2004), agricultural (Soto et al, 2015;Sun et al, 2015;Zhang et al, 2010), micro-organism (Stoppacher et al, 2010;Strobel et al, 2008), soil (Durovic et al, 2012;Eriksson et al, 2001), water Martínez et al, 2013;Morales et al, 2012), cosmetics (Ortiz and Tena, 2006;Yang et al, 2010), and food safety fields (Sang et al, 2013;Silva et al, 2015;Tait et al, 2014).…”
Section: Introductionmentioning
confidence: 99%